Tobacco and Lead Exposures and ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
The independent and joint effects of prenatal tobacco and childhood lead exposures on ADHD in a national sample of US children were studied by researchers at Cincinnatti Children's Hospital, OH; British Columbia Children's Hospital, Vancouver, Canada; and University of North Carolina, Chapel Hill, NC.